Prevalence and Correlates of Gastroesophageal Reflux Disease in Southern Iran: Pars Cohort Study - Zohre Khodamoradi (Middle East Journal of Digestive Diseases, 2017)
BACKGROUND Prevalence of gastroesophageal reflux disease (GERD) is increasing worldwide. We aimed to estimate the prevalence of GERD in Pars Cohort Study (PCS) and to find its correlates.